Sphingolipid Metabolism: A New Therapeutic Opportunity for Brain Degenerative Disorders - Di Pardo, Alba; Maglione, Vittorio (Frontiers in Neuroscience, 2018)
Neurodegenerative diseases represent a class of fatal brain disorders for which the number of effective therapeutic options remains limited with only symptomatic treatment accessible. Multiple studies show that defects in sphingolipid pathways are shared among different brain disorders including neurodegenerative diseases and may contribute to their complex pathogenesis. In this mini review, we discuss the hypothesis that modulation of sphingolipid metabolism and their related signaling pathways may represent a potential therapeutic approach for those devastating conditions. The plausible “druggability” of sphingolipid pathways is greatly promising and represent a relevant feature that brings real advantage to the development of new therapeutic options for these conditions. Indeed, several molecules that selectively target sphingolipds are already available and many of them currently in clinical trial for human diseases. A deeper understanding of the “sphingolipid scenario” in neurodegenerative disorders would certainly enhance therapeutic perspectives for these conditions, by taking advantage from the already available molecules and by promoting the development of new ones.